Perception of Affordances in Soccer: Kicking for Power Versus Kicking for Precision. Issue 1 (2nd January 2022) - Peker, Alper Tunga; Böge, Veysel; Bailey, George; Wagman, Jeffrey B.; Stoffregen, Thomas A.
ABSTRACT: Purpose : We investigated youth soccer players' perception of affordances for different types of kicks. Method : In the Power task, players judged the maximum distance they could kick the ball. In the Precision task, players judged how close to a designated target line they could kick the ball. Following judgments, players performed each task. Both judgments and performance were assessed immediately before and immediately after players competed in a regulation soccer match, thereby permitting us to assess possible effects of long-term experience on perceptual sensitivity to short-term changes in ability. We compared players from two league groups: U16 (mean age = 15.45 years, SD = 0.52 years) versus U18 (mean age = 17.55 years, SD = 0.52 years). Results : As expected, for the Power task actual kicking ability was greater for the U18 group ( p < .05). In statistically significant interactions, we found that judgments of Power kicking ability differed before versus after match play, but only for the U16 group. We found no statistically significant effects for the Precision task. Conclusions : We identified interactions between long-term and short-term soccer experience which revealed that the effects of long-term experience on affordance perception were not general. Two additional years of playing experience (in the U18 group, relative to the U16 group) did not lead to an overall improvement in the perception of kicking-related affordances. Rather, variation in long-term experience was associated with changes in affordance perception which were situation-specific, being manifested only after playing a soccer match, and not before.